STRATEGY TO INTEGRATE RELIGIOUS MODERATION IN THE QUR'AN HADITH CURRICULUM AT MADRASAH TSANAWIYAH LEVEL - Miswar (International Journal Multidisciplinary (IJMI), 2024)
Objective: The integration of religious moderation into the Qur'an Hadith curriculum at Madrasah Tsanawiyah faces several obstacles, such as teachers' limited understanding and skills in effectively teaching moderation values. Often, teaching still focuses on memorization and a literal understanding of the texts, failing to connect these teachings with the broader context of moderation. This study aims to describe and analyze the concepts, methods, and approaches used in integrating religious moderation into the Qur'an Hadith curriculum at the Madrasah Tsanawiyah level. Method: This research utilizes library research as its approach. The data sources for this study include scientific journal articles and research reports relevant to religious moderation and Islamic religious education. By reviewing these materials, the study seeks to identify best practices and frameworks for incorporating moderation into the curriculums. Results: The study found that the integration of religious moderation in the Qur'an and Hadith curriculum at Madrasah Tsanawiyah focuses on fostering a balanced and tolerant understanding that respects diversity. The core concept is wasatiyah (balance), which aims to prevent extremism in religious practices. The methods employed include contextual learning, discussions, role-play, and problem-based learning, which link moderation teachings to students' everyday lives and enhance their understanding through experiential learning. Novelty: The research applies an integrative and holistic approach to teaching religious moderation, addressing cognitive, affective, and psychomotor aspects of learning. This approach ensures that students not only understand the concept of moderation but also apply it in their attitudes and behaviors.